Effects of Hospital Base "Discharge Teaching" on Self-Care among Post Myocardial Infarction of Follow-Up Patients at Tertiary Care Hospital - Bai, Ranjeeta; Fatima, Musarat (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To determine the effectiveness of hospital-based discharge teaching on self-care among post-myocardial infarction patients. Methodology: This cross-sectional descriptive study was carried out at Cardiology Outpatient Department (OPD), Liaquat University Hospital Hyderabad, from April to October 2019, and data were collected from 180 follow-up post myocardial patients at cardiology OPD with first-time heart attack and stable angina at Liaquat University Hospital Hyderabad. Participants were approached through the purposive sampling method. Data analysis was done by Statistical Package for Social sciences (SPSS) version 20.0. Variables were calculated by frequency and percentage. A bar graph was used for graphical presentation for analysis. Results: There were 180 participants included in this study, 93 (51.7%) females and 87 (48.3%) male participants. The majority (78.3%) of the participants were from urban areas. It was observed that 98.3% of patients felt improvement, and 90% of participants were satisfied with discharge teaching. Conclusion: This study concluded that a well-organized discharge planning program is very effective treatment or intervention to improve patient health status. It can change life style behaviors of the patient and reduce complications and hospital readmissions. Keywords: Myocardial infarction, heart failure, hospital base discharge teaching